2020
DOI: 10.3389/fcell.2020.00270
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Quality Control Governed by Ubiquitin

Abstract: Mitochondria are essential organelles important for energy production, proliferation, and cell death. Biogenesis, homeostasis, and degradation of this organelle are tightly controlled to match cellular needs and counteract chronic stress conditions. Despite providing their own DNA, the vast majority of mitochondrial proteins are encoded in the nucleus, synthesized by cytosolic ribosomes, and subsequently imported into different mitochondrial compartments. The integrity of the mitochondrial proteome is permanen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 131 publications
(190 reference statements)
3
32
0
Order By: Relevance
“…There is no doubt that the mitochondrial quality control system is crucial to maintain mitochondrial proteostasis and for the dynamic adaptation of the mitochondrial proteome to changing metabolic conditions [9][10][11][12]. Nevertheless, studies over the past decade have shown that the ubiquitin-proteasome system (UPS) of the cytosol is of pivotal relevance for the surveillance of the mitochondrial proteome [13][14][15][16][17]. Particularly important in this context are the degradation of cytosolic mitochondrial precursor proteins and that of mitochondrial surface proteins, the so-called mitochondria-associated degradation (MAD), by the proteasome.…”
mentioning
confidence: 99%
“…There is no doubt that the mitochondrial quality control system is crucial to maintain mitochondrial proteostasis and for the dynamic adaptation of the mitochondrial proteome to changing metabolic conditions [9][10][11][12]. Nevertheless, studies over the past decade have shown that the ubiquitin-proteasome system (UPS) of the cytosol is of pivotal relevance for the surveillance of the mitochondrial proteome [13][14][15][16][17]. Particularly important in this context are the degradation of cytosolic mitochondrial precursor proteins and that of mitochondrial surface proteins, the so-called mitochondria-associated degradation (MAD), by the proteasome.…”
mentioning
confidence: 99%
“…The two main proteolytic pathways of the PQC network, the autophagy-lysosomal system and the UPS, can also impact genome integrity. Not only do they mitigate oxidative DNA damage by controlling mitochondrial quality (Pickles, Vigié, and Youle 2018;Ravanelli et al 2020), they also influence the dynamics of genome maintenance by controlling the turnover of many key DNA repair proteins (Brinkmann et al 2015;Guo and Zhao 2020 ) and the DNA replication machinery (Roseaulin et al 2013;Walter et al 2016). Autophagy also appears to play a key role in maintaining nuclear homeostasis by selectively degrading other nuclear components (i.e.…”
Section: The Pqc Network Is Crucial To Maintain Genome Integritymentioning
confidence: 99%
“…By serving as a cell death gatekeeper, mitochondria play a central role in cellular quality control and survival decisions. Here, formation of the mitochondrial permeability transition pore and ERAD, Cdc48/p97 and the proteasome assist mitochondrial-associated degradation (MAD) [29,[64][65][66][67] ( Figure 1). Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, mitochondrial integrity relies on protein import. In addition, mitochondrial homeostasis is maintained by a set of quality control machineries, namely internal proteases, chaperones, and the ubiquitin proteasome system (UPS) [ 27 , 28 , 29 , 30 ]. The UPS is mostly prevalent for proteins resident in the OMM, but also impacts others, e.g., during their import into mitochondria.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation